Research on optimization strategies of university ideological and political parenting models under the empowerment of digital intelligence - Fan Lv (Scientific Reports)
Abstract The development of big data, artificial intelligence, cloud computing, and other new generations of intellectual technologies has triggered digital changes in university civic education’s resources, forms, and modes. It has become a new engine to promote the innovation and development of the civic education model. Digital and intellectual technology-enabled university civic and political education model can carry the concept of innovation through the subject, content, process, and scene of education and promote the development of the ideological and political parenting model in the direction of refinement, specialization, and conscientization. Based on the differential game model, this paper comprehensively considers the model characteristics of universities, enterprises, and governments and their intertemporal characteristics of collaborative parenting and innovation behaviors. It constructs the no-incentive, cost-sharing, and collaborative cooperation models, respectively, and obtains the optimal trajectories for the degree of effort, the subsidy coefficient, the optimal benefit function, and the digital and intelligent technology stock. The conclusions are as follows: (1) resource input cost and technological innovation cost are the key driving variables of university ideological and political parenting; (2) the government’s cost subsidy improves the degree of innovation effort of universities and enterprises, and thus achieves Pareto optimality for the three parties; (3) the degree of innovation effort, overall benefit and technology level of the three parties in the synergistic cooperation model is better than that of the other two models. Finally, the validity of the model is verified through numerical simulation analysis. An in-depth discussion of the digital intelligence-enabled ideological and political parenting model is necessary for the high-quality development of education, which helps improve the scientific and practical ideological and political parenting in the digital age.